Nano Drug Delivery System for Tumor Immunotherapy: Next-Generation Therapeutics - Zhou, Lili; Zou, Manshu; Xu, Yilin; Lin, Peng; Lei, Chang; Xia, Xinhua (Frontiers in Oncology, 2022)
Tumor immunotherapy is an artificial stimulation of the immune system to enhance anti-cancer response. It has become a powerful clinical strategy for treating cancer. The number of immunotherapy drug approvals has been increasing in recent years, and many treatments are in clinical and preclinical stages. Despite this progress, the special tumor heterogeneity and immunosuppressive microenvironment of solid tumors made immunotherapy in the majority of cancer cases difficult. Therefore, understanding how to improve the intratumoral enrichment degree and the response rate of various immunotherapy drugs is key to improve efficacy and control adverse reactions. With the development of materials science and nanotechnology, advanced biomaterials such as nanoparticle and drug delivery systems like T-cell delivery therapy can improve effectiveness of immunotherapy while reducing the toxic side effects on non-target cells, which offers innovative ideas for improving immunity therapeutic effectiveness. In this review, we discuss the mechanism of tumor cell immune escape and focus on current immunotherapy (such as cytokine immunotherapy, therapeutic monoclonal antibody immunotherapy, PD-1/PD-L1 therapy, CAR-T therapy, tumor vaccine, oncolytic virus, and other new types of immunity) and its challenges as well as the latest nanotechnology (such as bionic nanoparticles, self-assembled nanoparticles, deformable nanoparticles, photothermal effect nanoparticles, stimuli-responsive nanoparticles, and other types) applications in cancer immunotherapy.